Ultrastructure of Leydig cells in human ageing testes. - Paniagua, R (1986)
Ultrastructural study of Leydig cells in elderly men revealed the following Leydig cell types: (1) ultrastructurally normal Leydig cells (46.2%); (2) Leydig cells either with multiple cytoplasmic or intranuclear Reinke crystals or with numerous para-crystalline inclusions (6.1%); (3) multivacuolated Leydig cells with the cytoplasm almost filled by lipid droplets (16.7%; (4) dedifferentiated Leydig cells with poor development of agranular endoplasmic reticulum and mitochondria, and increased amounts of lipofuscin granules (22.3%); and (5) bi- or trinucleate Leydig cells (8.7%) showing either a normal (2.8%) or dedifferentiated (5.9%) cytoplasm. These results suggest an involution of Leydig cells with advancing age. A correlation between the proportion of altered Leydig cells and the decrease in testosterone and increase in luteinising hormone levels could be observed.